Capital Shallowness: A Problem for New Zealand? - Julia Hall; Grant Scobie (New Zealand Government, The Treasury, 2005)
There is now substantial evidence that New Zealand's overall rate of economic growth relative to Australia's has been lower in part because of lower levels and slower growth in our labour productivity. This then requires us to explore why the labour productivity is lower in New Zealand. This paper explores the extent to which a lower level of capital per hour worked (or lower capital intensity) is associated with less output per hour worked in New Zealand. We find that the capital intensity in New Zealand has not been increasing as fast as in Australia for nearly 25 years. Between 1995 and 2002, lower capital intensity explains 70 percent of the difference in output per hour worked. Whereas the cost of labour relative to capital has been rising in Australia, it has fallen by 20 percent in New Zealand between 1987 and 2002. The relative price of labour to capital in New Zealand fell to 60 percent of the Australian value in 2002 after being comparable in the late 1980's. It is to be expected that New Zealand enterprises would therefore tend to adopt less capital intensive production methods. Differences in capital intensity could also have arisen because the underlying production technologies are different even if the relative prices of labour and capital in the two economies had been similar. We explore this issue and find a similar response of capital intensity to changes in the wage rate relative to the return on capital for the economies as a whole. However when we exclude the mining sector we find that the responsiveness in New Zealand is about one half that of Australia. Whether there are impediments or greater uncertainty in New Zealand that limit the ability of firms to respond to economic signals as much as their Australian counterparts remain as possible explanations requiring further investigation.
Keywords: E22; E23; E24; O49; 330; New Zealand; Australia; Capital-labour ratios; relative factor prices